PENGARUH MODEL PEMBELAJARAN INKUIRI TERBIMBING TERHADAP HASIL BELAJAR PENGETAHUAN KONSEPTUAL SISWA PADA MATERI POKOK FLUIDA STATIS - Dewi, Rosita; Sinuraya, Juru Bahasa (JURNAL IKATAN ALUMNI FISIKA, 2017)
The purpose of reseach to investigate the effect of guided inquiry learning model on students conceptual knowledge in fluid static topic at XI class semester II SMA Negeri 1 Salapian A.y.2015/2016. This reseach was quasi experiment. The population was all student of class XI semester IIÂ  consided 3 class. Sampling was done by cluster random sampling XI IPA 2 selected as experiment class while XI IPA 1 as control class. The instruments used in the essay test form and observation sheet to measure activity learning student. Result of research obtained average pretest value of experiment class 25.82 while the average pretest value of control class 22.38. The average postest value of experiment class 79.05 while the average postest value of control 72.08. During the learning process the activity average value of student in experiment class 72.29 included active criterion. Proved hypothesis on result student learn to effect of guided inquiry model was better than conventional learning in fluid static topic.